Novel topical esmolol hydrochloride improves wound healing in diabetes by inhibiting aldose reductase, generation of advanced glycation end products, and facilitating the migration of fibroblasts - Kulkarni, Sudhir A.; Deshpande, Supreet K.; Rastogi, Ashu (Frontiers in Endocrinology, 2022)
Abstract Aims/Objectives: Wound healing in people with diabetes is delayed secondary to impaired nitric oxide generation, advanced glycation end-products (AGE) and poor migration of epithelial cells. To develop novel topical esmolol hydrochloride (Galnobax) and assess its efficacy for wound healing in streptozocin-induced diabetic hairless rat. Methods: All experiments were performed at the animal laboratory and tertiary care research facility. A docking study of Esmolol was performed using Grid-based PLP docking method. Aldose reductase inhibition was assessed from enzyme obtained from bacterial culture (spectrophotometer); sorbitol content in homogenized RBCs and advanced glycation end products (AGE) in glucose and bovine serum (BSA) by fluorometry following addition of esmolol in varying concentrations (ex-vivo). Scratch assay of human fibroblasts, endothelial cells, and keratinocytes under high glucose environment and after esmolol was studied by phase contrast microscopy. Efficacy evaluation of topical application of Galnobax 14% and 20% or vehicle was conducted in streptozotocin-induced diabetic hairless rats with assessment of endogenous nitrite and hydroxyproline from homogenised wound tissue. A pharmacokinetic and dermal toxicity of varying concentration of esmolol was assessed in Hanford miniature-swine, skin irritation in New-Zealand white rabbit and sensitization potential in Hartley-strain Guinea Pig. Results: Esmolol significantly (59%) inhibited the formation of sorbitol in erythrocytes by inhibiting aldose reductase (IC50 150 µM) in comparison to glucose-induced sorbitol levels. AGEs in bovine serum albumin were significantly reduced at 1mM esmolol concentrations (2.6±1.7) similar to that of diclofenac (2.5±1.3). Esmolol at 1µm and 10µM significantly enhanced migration of fibroblasts, epithelial cells and keratinocytes as compared to control. The nitric oxide levels were 44% and 112% higher with Galnobax (14%) than diabetic control and vehicle control respectively. The day-7 and day-14 hydroxyproline in the wound was higher by 22% and 44%; 6% and 13% with Galnobax (14%) compared to diabetic control and vehicle control groups, respectively. Wound area significantly reduced with Galnobax 14% up to day-10 compared to controls. The pharmacokinetic and dermal toxicity in miniature swine suggested no significant adverse event with Galnobax. Conclusions: Topical esmolol hydrochloride is a novel, safe and effective treatment modality that act through pleotropic mechanisms to hasten wound healing in diabetes.